Avaliação da cicatrização de feridas por hidrogel contendo extrato seco padronizado de Hyptis pectinata (L.) em ratos - Freitas, Anderson Leite (2018)
The veined ulcers are a very common problem and his very expensive treatment. The World-wide Organization of Health and Brazil they have been stimulating the use of medicinal plants. For so much we have like objective: 1) to Carry out a systematic revision about the fitoterápicos with activity cicatrizante, 2) to Develop and to validate an analytical methodology for quantificação of the aqueous extract and products been derived from Hyptis pectinata (L.) 3) to Investigate the potential cicatrizante of the standardized dry extract of H. pectinata when to check possible alterations of the standardized dry extract of H. pectinata incorporated to a hidrogel, in the process of scarring of induced cutaneous wounds was incorporated to a hidrogel in model tecidual of injured in mice, 4). The inquiry looked in Portuguese, Englishman and Spaniard, in the bases of data: Cinahl, Lilacs, Medline/Pubmed, Scopus and Web of Science, using the descritores: Plants, Medicinal, Wound Healing and Varicose Ulcer. The search of the systematic revision produced 3.505 articles, being that seven were selected for inclusion in the revision. Of the included studies, seven (100 %) valued the reduction of the area of ulcer, four (57,14 %) valued reepitelização, two (28,57 %) valued the bacterial flora and one (14,28 %) valued the pressure of oxygen and carbon dioxide percutâneo. A mark-analysis was carried out in two studies that analysed the effects of the hidrogel incorporated with Mimosa tenuiflora in the treatment of the veined ulcer and included 42 patients, with middle age of 60,5 years, and middle duration of treatment of 10,5 weeks. It was valued the heterogeneity using I2, when it turned in a high value of 84 %. The hidrogel that it incorporated M. tenuiflora seemed to be a promising candidate for the treatment of veined ulcers. An analytical method was developed and validated for cromatografia liquid of high efficiency for the substances quantificação in the aqueous extract of H. pectinata according to resolution RDC 899 of the Anvisa. The method presented boa repetibilidade, strength, exactness, especificidade, reproductiveness and intermediary precision. For the evaluation of the activity cicatrizante experiments were carried out with 3, 7 and 14 days in animal models. The injuries treated with HP5 in the time of 3 days obtained a significant reduction (p<0,05) regarding the group control (CTL). In the injuries accompanied by 14 days treated with HP5 there was a significant reduction (p<0,05) regarding the injuries of the group treated with CTL. In the analysis histomorfológica of the scores of the group treated by 3,7 and 14 days there was no significant difference between the group CLT and the group HP5. The results suggest that the hidrogel of H. pectinata presented improvement in the repair cicatricial in animal, but precise model of more studies to corroborate with the finds of this study.